2008
DOI: 10.1016/j.apsusc.2007.07.154
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of photocatalytic degradation of polyethylene plastic with CuPc modified TiO2 photocatalyst under solar light irradiation

Abstract: Solid-phase photocatalytic degradation of polyethylene (PE) plastic, one of the most common commercial plastic, over copper phthalocyanine (CuPc) modified TiO 2 (TiO 2 /CuPc) photocatalyst was investigated in the ambient air under solar light irradiation. Higher PE weight loss rate, greater texture change; more amount of generated CO 2 , which is the main product of the photocatalytic degradation of the composite PEC plastic can be achieved in the system of PE-(TiO 2 /CuPc) in comparison with PE-TiO 2 system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(62 citation statements)
references
References 23 publications
1
61
0
Order By: Relevance
“…Therefore, it seems that the composition of plastic with TiO 2 nanoparticles is a useful means to decompose solid polymer in the open air. Researchers have recently studied the solid-phase photocatalytic degradation of polymer-TiO 2 nano-composite [8][9][10][11][12] . But the photodegradation properties of PP nano-composites has rarely been studied.…”
Section: Hoomentioning
confidence: 99%
“…Therefore, it seems that the composition of plastic with TiO 2 nanoparticles is a useful means to decompose solid polymer in the open air. Researchers have recently studied the solid-phase photocatalytic degradation of polymer-TiO 2 nano-composite [8][9][10][11][12] . But the photodegradation properties of PP nano-composites has rarely been studied.…”
Section: Hoomentioning
confidence: 99%
“…Further, TiO 2 /dye (dye based on metal-phthalocyanine (MPc), e.g., CuPc) systems have also been used as composite photocatalysts to accelerate the degradation of PS and PE under solar radiation at ambient conditions [69,70]. For these TiO 2 /dye polymer systems, it was demonstrated that, under outdoor solar exposure conditions, the amount of CO 2 released (the main product of photocatalytic degradation) and other volatile organic compounds, and the corresponding weight loss, of PE-(TiO 2 /CuPc) films were much higher than that of a PE-TiO 2 films, and both were very much higher than is the case for unmodified PE film exposed under the same conditions, indicating chain scission due to the photocatalytic action of TiO 2 , which is further enhanced in the presence of the dye [70].…”
Section: Polymersmentioning
confidence: 99%
“…TiO 2 catalyst is typically immobilized on inorganic oxide substrates, but rarely on polymer surfaces because photocatalysis tends to degrade the polymer. 34,35 The main ways to attach TiO 2 particles to polymer substrates are physical and chemical fixing. [20][21][22][23][24][25][26][27][28]36 In the case of polyethylene (PE), fixing methods include ironing of PE film sprinkled with TiO 2 powder, 21 embedding PE film into TiO 2 suspension and heating, 22,23 and hot pressing.…”
Section: Introductionmentioning
confidence: 99%